2014
DOI: 10.1002/mds.25810
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency subthalamic nucleus stimulation in Parkinson's disease: A randomized clinical trial

Abstract: Low-frequency stimulation via the optimal contacts is effective in improving overall motor function of patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 15 publications
9
107
1
1
Order By: Relevance
“…However, it could be impractical to conduct studies with such a sample size of persons with PD who underwent STN-DBS. Moreover, the sample size used in the current study is representative of the sample sizes used in the literature studying balance and gait in persons with PD who underwent STN-DBS [10,12,14,16,23,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it could be impractical to conduct studies with such a sample size of persons with PD who underwent STN-DBS. Moreover, the sample size used in the current study is representative of the sample sizes used in the literature studying balance and gait in persons with PD who underwent STN-DBS [10,12,14,16,23,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Phibbs et al (2013) reported no improvements in stride length at low-frequency stimulation among persons with PD who did not present such gait-related impairments after highfrequency STN-DBS [29]. Using only UPDRS-III motor scores, Khoo et al (2014) showed that low-frequency stimulation may be better if stimulated at more optimal contacts [30]. In the present study we have attempted to address the need for more quantitative evidence to determine the effects of low-frequency STN-DBS on static postural control, dynamic postural control (gait initiation) and gait among consecutive group of typical persons with PD undergoing deep brain stimulation surgery.…”
Section: Introductionmentioning
confidence: 98%
“…Lowering the amount of charge involved in biphasic waveforms, and thus the electrical energy involved, equated to more patient comfort as well as less damage to the surrounding tissue of the electrode [12] . Similarly, recent work in deep brain stimulation shows that low-frequency stimulation may similarly affect motor symptoms in Parkinson's disease patients compared to HFS, which is traditionally used [15] . This further provides evidence that changing the parameters of stimulation is paramount for optimizing effectiveness and, at a minimum, is worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…maintained at LFS for up to 15 months, with 5 showing a clinical global improvement on the scale. All on dorsal except 1 on ventral contacts.[13]Sidiropoulos et al, 201345Non-randomized non-blindedOnNot specified, but axial impairment with no satisfactory benefit from HFS60–80 Hz/130–185 Hz(6 on 60 Hz, 39 on 80 Hz)111.5 days,(the median, up to 4 years)NoF/U: overall, no improvement with LFS on any of the measures in UPDRS III motor, axial, gait, and speech subscores, and self-reported number of falls.[9]Khoo et al, 201414Randomizeddouble blindedOnNo FOG at medication ON assessment, but most had FOG at medication OFF by history.60 Hz/130 HzNo long term follow upYesAcutely: mean UPDRS III score, axial motor subscore and akinesia subscores were improved for LFS. Also, less time and fewer steps to complete the 10-m walk and a tendency of improving the balance.…”
Section: Lfs Versus Hfs On Swallowing Functionmentioning
confidence: 99%